Interventional Procedures for Vertebral Diseases: Spinal Tumor Ablation, Vertebral Augmentation, and Basivertebral Nerve Ablation—A Scoping Review - Vincius Tieppo Francio (MDPI AG, 2021)
Low back pain is consistently documented as the most expensive and leading cause of disability. The majority of cases have non-specific etiologies. However, a subset of vertebral diseases has well-documented pain generators, including vertebral body tumors, vertebral body fractures, and vertebral endplate injury. Over the past two decades, specific interventional procedures targeting these anatomical pain generators have been widely studied, including spinal tumor ablation, vertebral augmentation, and basivertebral nerve ablation. This scoping review summarizes safety and clinical efficacy and discusses the impact on healthcare utilization of these interventions. Vertebral-related diseases remain a top concern with regard to prevalence and amount of health care spending worldwide. Our study shows that for a subset of disorders related to the vertebrae, spinal tumor ablation, vertebral augmentation, and basivertebral nerve ablation are safe and clinically effective interventions to decrease pain, improve function and quality of life, and potentially reduce mortality, improve survival, and overall offer cost-saving opportunities.